2019
DOI: 10.1101/695254
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular insights from conformational ensembles via machine learning

Abstract: Biomolecular simulations are intrinsically high dimensional and generate noisy datasets of everincreasing size. Extracting important features in the data is crucial for understanding the biophysical properties of molecular processes, but remains a big challenge. Machine learning (ML) provides powerful dimensionality reduction tools. However, such methods are often criticized to resemble black boxes with limited human-interpretable insight.We use methods from supervised and unsupervised ML to efficiently create… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 77 publications
0
20
0
Order By: Relevance
“…A previous study using MLP to identify important residues between different protein configurations showed that more hidden layers led to lower accuracy. 34 Here, we reached an accuracy of 1 for classifying SARS-CoV from SARS-CoV-2 with only one hidden layer in the MLP implementation. If we remove all hidden layers of an MLP model, it will have the same architecture as a linear model, such as the LR approach also used here, for which the accuracy was 1 as well.…”
Section: Discussionmentioning
confidence: 69%
“…A previous study using MLP to identify important residues between different protein configurations showed that more hidden layers led to lower accuracy. 34 Here, we reached an accuracy of 1 for classifying SARS-CoV from SARS-CoV-2 with only one hidden layer in the MLP implementation. If we remove all hidden layers of an MLP model, it will have the same architecture as a linear model, such as the LR approach also used here, for which the accuracy was 1 as well.…”
Section: Discussionmentioning
confidence: 69%
“…Their power in finding important information out of large amount of data has been exploited by the biochemistry community, many interesting applications have been showcased in the literature. Recently, Fleetwood et al 30 have demonstrated its capability in learning ensemble properties from molecular simulations and providing easily interpretable metrics describing important structural or chemical features. The machine-learning analysis of our trajectories is based on the demystifying package from Fleetwood et al 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Fleetwood et al 30 have demonstrated its capability in learning ensemble properties from molecular simulations and providing easily interpretable metrics describing important structural or chemical features. The machine-learning analysis of our trajectories is based on the demystifying package from Fleetwood et al 30 . Residues highlighted as providing a significant contribution to the MutM:DNA bonding by the MLP analysis are in agreement with data from the literature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations